Optimasi Suhu Annealing Tiga Regio Berbeda Isolat Multidrug Resistance Mycobacterium Tuberculosis dengan Metode Multiplex Polymerase Chain Reaction (ANNEALING TEMPERATURE OPTIMIZATION ON THREE DIFFERENT REGIONS OF MYCOBACTERIUM TUBERCULOSIS MULTIDRUG RESI - Adikara, Indra Juana; Wirajana, I Nengah; Yowani, Sagung Chandra (Jurnal Veteriner, 2017)
Multiplex PCR is a method used to amplify more than one target sequences simultaneously. The aimof this research was to optimize PCR on the region of inhA promoter, inhA gene and katG gene usingMultidrug Resistance Tuberculosis (MDR-TB) Isolate. Isolation of DNA was done by using High Pure PCRTemplate Preparation Kit. Amplification process was done by Multiplex PCR usingthree pairs primers i.e.mabA-inhA-promoter-FS and mabA-inhA-promoter-R,inhA (F) and inhA (R) and KG24F and KG60R.Amplification process started by predenaturation at 95°C for 15 minutes, followed by 45 cycles consistingof denaturation at 94°C for 1 minute, annealing at 56°C, 57°C and 58°C for 1 minute and 20 seconds andextension at 72°C for 2 minutes. Then it is finished by postextension at 72°C for 10 minutes. PCR productwas detected by electrophoresis and visualized under UV Transiluminator. Annealing temperature of56°C resulted in a thicker, clearerandaccording to the desired size as compared to that of with 57°C and58°C. Conclusion that obtained was annealing temperature 56°C was optimum annealing temperatureon inhA promoter, inhA gene and katG gene region of Mycobacterium tuberculosis Multidrug Resistanceisolate using Multiplex Polymerase Chain Reaction.
Keywords: multi-drug resistance mycobacterium tuberculosis (MDR-TB); multiplex polymerase